PERAN SOSIAL MEDIA DALAM MENINGKATKAN PARTISIPASI PUBLIK DALAM PROSES PERENCANAAN ANGGARAN DI KOTA SEMARANG - Widyaningsih, Ria Ekanindya (Gapenas Publisher, 2024)
This study aims to analyze the influence of social media users on government budgeting in the City of Semarang, considering the mediating role of public trust and the moderating roles of social media users' perceptions and the ease of social media usage. The population of this study consists of all residents of the City of Semarang, with a total of 400 respondents. Data collection was conducted by distributing questionnaires online and randomly via Instagram and WhatsApp platforms. The analysis technique used is Structural Equation Modeling-Partial Least Square (SEM-PLS) to test direct, indirect, and moderation effects. The results indicate that social media users have a direct influence on budgeting, with significant roles played by the moderating variables of users’ perceptions of social media and the ease of social media usage. The variable of users’ perceptions of social media moderates by strengthening the influence of social media users on budgeting, whereas the ease of social media usage moderates by weakening the influence, although still significant. Social media users also have an indirect positive and significant influence on budgeting through the mediating variable of public trust, meaning that public trust in the government during the budgeting process can be enhanced through interactions or transparency facilitated by social media users. In the structural model testing, the Adjusted R-Square value is 0.295, indicating that the model's ability to explain the budgeting variable (endogenous) is relatively low, with the remaining influence attributed to other independent variables not measured in this study. Future research is recommended to include other variables that may influence budgeting and to adopt a qualitative approach to explore the relationships among the variables found